Colombia : Bank Financing to Small- and Medium-Sized Enterprises (SMEs) in Colombia - World Bank (Washington, DC, 2012)
Small-and Medium-Sized Enterprises (SMEs) represent an important part of the Colombian economy, although they are not well documented in official statistics. In particular, there does not exist sufficient periodic data as to their characteristics, evolution, or overall contribution to the economy - in most cases, SMEs tend to be bundled together with micro enterprises in official statistics. The true size of the market is understated due to informality. Lack of access to finance has been cited as an important problem in recent surveys. However, there are significant differences in perceptions as to the size and causes of the financing gap. While there is strong evidence to support its existence following the 1999 crisis, the significant growth of this market in recent years raises some questions as to whether such perceptions remain valid. One of the lessons of the last few years is that banks will expand SME lending on their own accord - in spite of the presence of important constraints - when they perceive the attractiveness of this market and have begun to saturate easier (in terms of business model) market segments such as corporate and consumer lending. However, in order to ensure the sustainable growth of this market, continued strong macroeconomic performance and a stable and consistent policy framework in the financial sector have been identified as important considerations.